Fertility counseling in women with hereditary cancer syndromes. (March 2022) - Somigliana, Edgardo; Costantini, Maria Paola; Filippi, Francesca; Terenziani, Monica; Riccaboni, Alessandra; Nicotra, Valeria; Rago, Rocco; Paffoni, Alessio; Mencaglia, Luca; Magnolfi, Stefania; Zuccarello, Daniela; Rienzi, Laura; et al.
Graphical abstract: Abstract: Hereditary cancer syndromes are a heterogeneous group of genetic conditions that are associated with an increased risk of developing cancer during lifespan. In affected women, parenthood may be accompanied by concerns for the offspring, considering the common autosomal dominant inheritance. Moreover, fertility preservation to prevent the detrimental effects of cancer treatments differs compared to other clinical contexts. The necessity to preserve gametes is indeed predictable and expected to be common. For these reasons, we advocate a personalized and early fertility counseling. Carriers should be aware of the risk of transmission. The possibility to perform elective oocytes cryopreservation, either before (previvors) or after (survivors) cancer diagnosis should be discussed. Finally, they should be informed about the options of preimplantation genetic test (PGT) and oocytes donation. In conclusion, physicians engaged in oncofertility should personalize the counseling for women with hereditary cancer syndromes, being aware of their peculiar needs.